Height and Diameter Relationship of Tectona Grandis L. in Mullaitivu District of Sri Lanka - Satheesan, T.; Sivachandiran, S.; Pushpakumara, D.K.N.G; Jeyavanan, K. (Research gate, 2017)
The study was carried out at different forest plantation sites of the teak (Tectona grandis L.) namely Mulliyawalai, Theravil, Mankulam and Karripatammuripu in Mullaitivu district of Sri Lanka. The study aims to interpret the relationship of tree height and canopy diameter over stem diameter at breast height. Teak plantation from Mankulam site was 13 years old young plantation and Karripatammuripu site was 35 years age old plantation. Theravil and Mankulm sites were 22 medium and even age old plantation. A total of 757 individuals of teak were assessed to determine relationship between height and diameter. Even aged planation of Mulliyawalai and Theravil sites showed a polynomial and linear curves relationship, respectively. High regression value (r2 ) was found in tree height over stem diamter (dbh) in Karripatammuripu site compared to other teak plantation site, showed that Karripatammuripu was found to be superior and clear site variation to others. In this fitted curves, Mulliyawalai, Theravil and Mankulam had lower regression (r2 ) values. Polynomial curve was best fitted in Mulliyawalai and Mankulam sites. Linear and logarithmic curves were fitted to Theravil and Karripatammuripu sites. Similarly, the Mulliyawalai site showed a clear site variation in canopy diameter over stem diameter. The site Mulliyawalai was found to be superior to others in canopy diameter over stem diameter. Linear curve was fitted to canopy diameter over stem diameter in Mankulum site. The behavior of the curves showed different pattern and models due to variation found on age, spacing, and other factors at forest plantation sites of the district in Sri Lanka
Keywords: Canopy; Diameter; Forest-Plantation; Height; Teak; Mullaitivu; Sri Lanka